Disorders of the upper limb on the operated side of the breast in women surgically treated for breast cancer - Rząca, Marcin Stanisław; Sołowiej, Krzysztof; Łukasiewicz, Sergiusz; Stanisławek, Andrzej; Węgorowski, Paweł (Journal of Education, Health and Sport, 2019)
Admission: Breast cancer is a cancer whose incidence is steadily increasing in the developed countries as well as in Poland. Treatment includes surgical treatment, which is the primary method of treatment, but give complications. The goal of the work It is to present the disorders occurring limb on the operated side of the breast in women surgically treated for breast cancer Material and methods: The study involved 151 women surgically treated for breast cancer (T1-4 N0-3 M0) in the Oncology Center of the Lublin Region St. John of Dukla in Lublin in 2013-2015. Results Disorders manifesting various symptoms arising as a consequence of surgery limb occurred in more than half of all patients (60%). Secondary lymphedema after 6 months occurred in 29 women (19.2%). The limb on the operated breast tingling was observed in 32% of patients, numbness in 24% of patients, heaviness limbs in 15% of patients, limb sensation spreading in 15% of patients, ache in 30% of patients. Discomfort limb armpit and accompanied by 21% of respondents. Conclusions: 1. The frequency of combining elderly disorders on the side of the operated breast is high. 2. Disorders upper limb on the operated side breast are more common if done axillary lymph nodes dissection. 3. Disorders upper limb on the operated side breast occur more frequently if there is secondary lymphedema. Streszczenie Wstęp: Rak piersi jest nowotworem, którego częstość występowania stale zwiększa się w krajach wysokorozwiniętych a także w Polsce. Leczenie obejmuje między innymi terapię chirurgiczną, która jest podstawową metodą leczenia, ale daje powikłania. Celem pracy jest przedstawienie zaburzeń występujących obrębie kończyny po stronie operowanej piersi u kobiet leczonych chirurgicznie z powodu raka piersi Materiał i metody: W badaniu udział wzięło 151 kobiet leczonych chirurgicznie z powodu raka piersi (T1-4 N0-3 M0) w Centrum Onkologii Ziemi Lubelskiej św. Jana z Dukli w Lublinie w latach 2013-2015. Wyniki: Zaburzenia manifestujące się różnymi objawami powstałymi w konsekwencji zabiegu w obrębie kończyny wystąpiły u ponad połowy wszystkich badanych (60%). Wtórny obrzęk limfatyczny po 6 miesiącach wystąpił u 29 kobiet (19,2%). W obrębie kończyny po stronie operowanej piersi mrowienie zostało zaobserwowane u 32% pacjentek, drętwienie u 24% pacjentek, uczucie ciężkości kończyny u 15% badanych, uczucie rozpierania w kończynie u 15% badanych, ból u 30% badanych. Uczucie dyskomfortu w obrębie kończyny i dołu pachowego towarzyszyło 21% badanych. Wnioski: 1. Częstość występowania zaburzeń w obrębie kończyny po stronie operowanej piersi jest duża. 2. Zaburzeń w obrębie kończyny po stronie operowanej piersi występują częściej, jeśli wykonano limfadenektomię dołu pachowego. 3. Zaburzeń w obrębie kończyny po stronie operowanej piersi występują częściej, jeśli występuje wtórny obrzęk limfatyczny.